An Underdeveloped Region: the Imperatives of Reindustrialization (on the example of the North caucasian Federal District) - G. H. Batov; L. A. Khutova; T. M. Shogenov (Модернизация, инновация, развитие)
Purpose: the purpose of the study is to develop a methodological toolkit for reindustrialization in the branches of the material sphere of lagging and underdeveloped regions based on the use of information, communication and digital technologies.Methods: the study is based on the use of the methodology of the systems approach, the methodological apparatus of the information society theory, the use of methods of economic and statistical analysis, scientific abstraction, analogies and scientific generalizations. In the course of developing the proposed topic, classical and modern works of domestic and foreign scientists, statistical and empirical material prepared in the process of field research were used.Results: regions with different levels of development function in the country's economy. The greatest problems are associated with underdeveloped and problem regions, which, given their certain potential, cannot yet cope with their difficulties. The situation in which such regions are located requires the search for new mechanisms that will allow us to overcome unfavorable circumstances and embark on the path of highly stable development. Many problems can be solved on the basis of reindustrialization. This requires a transition to continuous digitalization processes, the use of digital technologies and software products that can ensure the development of production systems in the direction of creating a new technological order.Conclusions and Relevance: issues of digital and programmatic reindustrialization of the economy are especially aggravated in lagging and underdeveloped regions, where, due to the poorly diversified sectoral structure of the industry, there is a weak reaction to the formation of investment demand for the production of competitive goods. Such regions, to which the North Caucasian Federal District (NCFD) belongs, can solve problems when using digital and information technologies. The implementation of the proposed measures will allow the region to leave the zone of problems and depression.